Unlocking Peak Performance: Navigating Interpersonal Relationships, Work Facilities, and Work Procedures in the Tangerang City District Office - Atrisia, Marchela Indah; Kartono; Ahmad Fadhlullah; Sherly Astuti (TIJAB (The International Journal of Applied Business), 2025)
Background: Employee performance stands as a pivotal factor in bolstering the organization's vision and mission. However, at the Neglasari sub-district office in Tangerang City, several issues have been identified. These include ineffective communication and interaction among employees, insufficient work facilities and equipment, and the absence of clearly defined standard operating procedures (SOP). Such shortcomings can potentially undermine the consistency and quality of employee performance. Objective: The objective of this research endeavor is to assess the impact of work procedures, work facilities, and interpersonal relationships on employee performance within the Neglasari District office located in Tangerang City. Method: This is a quantitative study employing an associative methodology approach. The employed sampling methodology is probability sampling, specifically utilizing a questionnaire to conduct simple random sampling. Respondents for this survey comprised one hundred employees of the Neglasari subdistrict office. SPSS version 26 is utilized to process the data through multiple regression analysis. Results: Interpersonal relationships and work procedures were found to have a significant impact on employee performance, whereas work facilities did not demonstrate a positive correlation with employee performance. Conclusion: The results of concurrent experiments indicate that the variables of work procedures, work facilities, and interpersonal relationships have a substantial impact on employee performance.   Keywords: Employee Performance; Interpersonal Relationships; Work Facilities; Work Procedures.